Association between phase angle and coronary artery calcium score in patients on peritoneal dialysis - Reis, Fabricio Moreira; da Silva, Maryanne Zilli Canedo; Reis, Nayrana Soares do Carmo; Costa, Fabiana Lourenço; da Silveira, Caroline Ferreira da Silva Mazeto Pupo; Barretti, Pasqual; Martin, Luis Cuadrado; Bazan, Silméia Garcia Zanati (Frontiers in Nutrition, 2022)
Introduction: The phase angle (PhA) has been used as a nutritional marker and predictor of mortality in patients on peritoneal dialysis (PD). The coronary artery calcium (CAC) score has showed to predict the incidence of acute myocardial infarction and death from cardiovascular disease in these patients. However, the association between PhA and CAC score in patients on PD is not well established, which is the objective of this study. Methods: Cross-sectional study with patients on PD, followed up at a University Hospital, between March 2018 and August 2019. PhA was evaluated by unifrequency bioimpedance (BIA). The CAC score was calculated based on cardiovascular computed tomography, considering positive when greater than or equal to 100 Agatston and negative when less than 100 Agatston. Results: We evaluated 44 patients on dialysis, with mean age of 56 years and 11.7 months. In a univariate analysis, an association was observed between the CAC score, the presence of atherosclerotic plaque in the carotid artery, and the difference in systolic blood pressure in the upper extremities with the PhA. In the hierarchical multivariate logistic regression, only the coronary artery calcium score maintained an association with the PhA in the final model. Conclusion: The PhA is associated with a positive CAC score in patients on PD, and despite other factors, may be useful as a risk marker for coronary artery disease in this population.